Activation and expression of endogenous CREB‐regulated transcription coactivators (CRTC) 1, 2 and 3 in the rat adrenal gland. (14th December 2020) - Smith, Lorna I. F.; Zhao, Zidong; Walker, Jamie; Lightman, Stafford; Spiga, Francesca
Abstract: The activation and nuclear translocation of cAMP‐response element binding protein (CREB)‐regulated transcription coactivator (CRTC)2 occurs in the rat adrenal gland, in response to adrenocorticotrophic hormone (ACTH) and stressors, and has been implicated in the transcriptional regulation of steroidogenic acute regulatory protein (StAR). We have recently demonstrated the activation of CRTC isoforms, CRTC1 and CRTC3, in adrenocortical cell lines. In the present study, we aimed to determine the activation and expression of the three CRTC isoforms in vivo in relation to Star transcription, under basal conditions and following a robust endotoxic stress challenge. Rat adrenal glands and blood plasma were collected following i.v. administration of either an ultradian‐sized pulse of ACTH or administration of lipopolysaccharide, as well as under unstressed conditions across the 24‐hour period. Plasma ACTH and corticosterone (CORT) were measured and the adrenal glands were processed for measurement of protein by western immunoblotting, RNA by a quantitative reverse transcriptase‐polymerase chain reaction and association of CRTC2 and CRTC3 with the Star promoter by chromatin immunoprecipitation. An increase in nuclear localisation of CRTC2 and CRTC3 followed increases in both ultradian and endotoxic stress‐induced plasma ACTH, and this was associated with increased CREB phosphorylation and corresponding increases in Star transcription. Both CRTC2 and CRTC3 were shown to associate with the Star promoter, with the dynamics of CRTC3 binding corresponding to that of nuclear changes in protein levels. CRTC isoforms show little variation in ultradian expression or variation across 24 hours, although evidence of long‐term down‐regulation following endotoxic stress was found. We conclude that co‐transcription factors CRTC2 and, more clearly, CRTC3 appear to act alongside phosphorylated CREB in the generation of ultradian pulses of Star transcription, essential for the maintenance of basal StAR expression. Similarly, our findings suggest CRTC2 and CRTC3 mediate Star transcriptional initiation following an endotoxic stressor; however, other transcription factors are likely to be responsible for the long‐term up‐regulation of adrenal Star transcription. Abstract : The present study aimed to determine the in vivo dynamics of activation and expression of the three cAMP‐response element binding protein (CREB)‐regulated transcription coactivator (CRTC) isoforms in relation to adrenocorticotrophic hormone (ACTH)‐induced steroidogenic acute regulatory (StAR) transcription. Nuclear localisation and association of CRTC2 and CRTC3 at the Star promoter followed increases in plasma ACTH induced by ultradian and endotoxic stress activity. Corresponding with increased CREB phosphorylation and increases in Star transcription, we conclude that CRTC2 and CRTC3 appear to play a role as co‐transcription factors alongside phosphorylated CREB in the initiation of Star transcription.